Yoghurt Acid Whey Marination - The Case of Lamb and Beef Meat - Karageorgou, A; Orfanou, G; Petrou, I; Goliomytis, M; Theodorou, G; Politis, I; Simitzis, P (Journal of the Hellenic Veterinary Medical Society, 2025)
Yoghurt acid whey (YAW) is an effluent of yoghurt production and is related with enhanced risk of environmental pollution due to its great organic matter levels, which elicit an increased bio-logical oxygen demand. During the previous decades a great effort has been exerted in finding sustainable applications of YAW. Therefore, YAW utilization in meat processing industry could be considered as a feasible option, since immersion of meat in marinades made of natural compounds is a process that is in constant advance due to its beneficial implications on meat organoleptic characteristics. In the present study, several quality traits and oxidation status of beef and sheep meat were evaluated after their marination into YAW. Forty samples for each meat type were assigned at random to one of five following treatments: CON, in the absence of marination; T1 and T3, where meat was immersed into YAW for 15 and 10 h at 4℃ (pH of 4.5), respectively, or T2 and T4, where samples were treated as in the T1 and T3 group, respectively, while carvacrol was also incorporated at 0.5 g/L. As shown, meat shear force value was decreased as a result of YAW marination for 15 h in beef and sheep meat samples, while the other quality characteristics (pH, color, cooking loss) were not dramatically influenced. On the other hand, meat oxidative stability was also improved in both meat types. As it can be pointed out, beef and sheep meat soaking into YAW for 15 h improves tenderness, however this is not evident in case of 10 h of immersion. At the same time, oxidative stability was also improved as a consequence of YAW marination especially in beef meat and lower MDA values of lamb meat were observed in carvacrol supplemented groups.